Philological Issues in the Context of Translations of Tasso’s “Jerusalem Delivered” - Jrbashyan, Ashkhen; Mkryan, Ashot (Bulletin of Yerevan University B: Philology, 2025)
The article examines the metrical and translation-related debate surrounding two nearly simultaneous modern Armenian translations of Torquato Tasso’s “Jerusalem Delivered,” published by the Mekhitarists in the early 1910s (translated by Arsen Ghazikyan and Atanas Tiroyan). Initially, the discussion revolved around the choice of metrical form, as Ghazikyan translated the poem using the 11-syllable Armenian syllabic verse, whereas Tiroyan employed the “Armenian meter,” which had been widely used since the mid-19th century. To resolve this dispute between the two Mekhitarist translators and reach a reasonable conclusion, another renowned philologist, Hrant Nazaryants, intervened by sending a letter to Arsen Ghazikyan, requesting him to present his views. After receiving a detailed and extensive response, Nazaryants decided to publish it in full, hoping that Armenian philological thought would find it “valuable and intriguing.” Through this, he sought to draw broader attention to key issues in translation studies, especially since the translation of artistic verse was actively developing not only within the Mekhitarist congregation but also beyond its boundaries. Ghazikyan’s analyses are valuable as a systematic attempt to uncover the specific features of the translation process and the causes of translational errors. From this perspective, his observations align with the approaches of prominent translation theorists of the second half of the 20th century, such as Peter Newmark, John Catford, Jiří Levý, and others.